Stenotrophomonas in diversified cropping systems: friend or foe? - Kumar, Abhishek; Rithesh, Lellapalli; Kumar, Vikash; Raghuvanshi, Nikhil; Chaudhary, Kautilya; Abhineet,; Pandey, Abhay K. (Frontiers in Microbiology, 2023)
In the current scenario, the use of synthetic fertilizers is at its peak, which is an expensive affair, possesses harmful effects to the environment, negatively affecting soil fertility and beneficial soil microfauna as well as human health. Because of this, the demand for natural, chemical-free, and organic foods is increasing day by day. Therefore, in the present circumstances use of biofertilizers for plant growth-promotion and microbe-based biopesticides against biotic stresses are alternative options to reduce the risk of both synthetic fertilizers and pesticides. The plant growth promoting rhizobacteria (PGPR) and microbial biocontrol agents are ecologically safe and effective. Owning their beneficial properties on plant systems without harming the ecosystem, they are catching the widespread interest of researchers, agriculturists, and industrialists. In this context, the genus Stenotrophomonas is an emerging potential source of both biofertilizer and biopesticide. This genus is particularly known for producing osmoprotective substances which play a key role in cellular functions, i.e., DNA replication, DNA-protein interactions, and cellular metabolism to regulate the osmotic balance, and also acts as effective stabilizers of enzymes. Moreover, few species of this genus are disease causing agents in humans that is why; it has become an emerging field of research in the present scenario. In the past, many studies were conducted on exploring the different applications of Stenotrophomonas in various fields, however, further researches are required to explore the various functions of Stenotrophomonas in plant growth promotion and management of pests and diseases under diverse growth conditions and to demonstrate its interaction with plant and soil systems. The present review discusses various plant growth and biocontrol attributes of the genus Stenotrophomonas in various food crops along with knowledge gaps. Additionally, the potential risks and challenges associated with the use of Stenotrophomonas in agriculture systems have also been discussed along with a call for further research in this area.